(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the study of the ethnic identity of the Kyrgyz and Kazakhs through the existence of echoes of ancient pagan beliefs. Attempts are given to identify archaic motives of spiritual culture in the worldview of modern young people - representatives of Turkic peoples.